Relationship Between Heat and Troughs During a Transport Process of Heating the Pet Films - Sunami, Y.; Shoji, T.; Mohd Danial, Ibrahim (Penerbit UTHM, 2023)
Understanding the troughs caused during a heat treatment process is important for ensuring process stability and product quality in roll-to-roll (R2R) productions methodology. The purpose of this study is to confirm the relationship between heat and troughs during a transport process of heating where heat is applied over a wide range of area. The temperature and tension applied to the web during the heated transport process were measured in the experimental analysis. Results showed that the web were stretched in the web transport direction during the heat transfer process. However, troughs did not occur because the experiment was conducted below the glass transition temperature. The comparison between the web temperature obtained in the experimental analysis with the one-dimensional thermal conduction simulation for the temperature distribution of the web are also conducted in this paper. This simulation was performed using a non-Fourier model that can be used on microscales. Simulation results show that when the temperature is gradually raised, the amount of thermal conduction is reduced during transportation of the web. The thermal conduction of ballistic phonon is smaller than that of the diffuse phonon when compared at same distance. Even though there were differences between the experimental values and the simulation results, this is because it ignores the heat transfer and radiant heat transfer.